Comments on "Effect of Temperature on the Adsorption of Methylene Blue Dye onto Sulfuric Acid–Treated Orange Peel". Issue 1 (2nd January 2017) - Hai, Tran Nguyen
Abstract : This article aims to discuss (1) the misconception about the Freundlich exponent n, (2) the important role of presenting the complete adsorption isotherms, (3) the inaccurately cited information compared to the original papers, (4) misconception regarding calculation of adsorption thermodynamic parameters, (5) and invalid conclusions regarding the separation factor. The inconsistency errors between adsorption equilibrium data and the thermodynamic parameters were also discussed. Furthermore, the adsorption process cannot reach equilibrium with the low initial Methylene Blue concentrations (50–250 mg/L) at the solid/liquid ratio of 4 g/L, which results in invalid arguments and conclusions regarding the adsorption isotherm.